2019
DOI: 10.1017/s0268416019000158
|View full text |Cite
|
Sign up to set email alerts
|

Plague – a disease of children and servants? A study of the parish records of St Peter upon Cornhill, London from 1580 to 1605

Abstract: A study of the parish records of St Peter upon Cornhill in London from 1580 to 1605 revealed that children suffered a greater increase in mortality than adults in the plague years of 1593 and 1603, and servants accounted for the majority of deaths within the 15–24 age group. Some family groups avoided the plague altogether, others suffered a single burial, however in some cases, individuals within the same family household were buried within a short period of each other. The epidemiological pattern is complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Children were identified from the text as 'son of' or 'daughter of' the head of household. In a study of the parish of St Peter, Cornhill where ages at burials were recorded, it was found that, almost without exception, the ages of individuals recorded as 'children' were between 0 and 19 years [1]. Stillborn children were not included in this study and it was rare, indeed, for the gender to be recorded in such cases.…”
Section: Categorisation Of the Burial Datamentioning
confidence: 95%
See 4 more Smart Citations
“…Children were identified from the text as 'son of' or 'daughter of' the head of household. In a study of the parish of St Peter, Cornhill where ages at burials were recorded, it was found that, almost without exception, the ages of individuals recorded as 'children' were between 0 and 19 years [1]. Stillborn children were not included in this study and it was rare, indeed, for the gender to be recorded in such cases.…”
Section: Categorisation Of the Burial Datamentioning
confidence: 95%
“…As a source of data, we make use of the parochial registers transcribed and published by the Harleian Society as others have done previously [1,3,26]. In addition, the register of the parish of St Christopher le Stocks, which was privately published, was also utilised.…”
Section: Parochial Registersmentioning
confidence: 99%
See 3 more Smart Citations